Sistem Pakar dalam Mendeteksi Kerusakan Laptop dengan Metode Case Based Reasoning - Rahman, Harif A (Jurnal Sistim Informasi dan Teknologi, 2021)
Laptop is an electronic device that is very widely used today, so the damage to this tool is the most frequently found case. Very many laptop users do not understand the type and level of damage. So researchers conducted this research in making it easier for users to detect laptop damage earlier. This study uses an Expert System that functions as a substitute for experts as a media consultation. The method used is Case Based Reasoning of laptop damage data on Lutfi Computer. The results of this study can detect damage more quickly and precisely in helping users to find the right solution to overcome the damage. So this research is very helpful for laptop users in general in overcoming early on accurately, so users can determine an accurate solution in dealing with damage to their laptops.